Diagnostic Imaging for Distal Extremity Injuries in Direct Access Physical Therapy: An Observational Study - Michael S Crowell; John S Mason; Jamie B Morris; Max K Dummar; Paul A Kuwik (International Journal of Sports Physical Therapy)
# Background